ANALYSIS OF CLIMATE ÃâÃâ TOURISM RELATIONSHIP USING TOURISM CLIMATE INDEX (TCI) (Case Study: Java and Bali) - HIKMAT KURNIAWAN (NIM: 22412309); Pembimbing: Dr. Rusmawan Suwarman, M.Si, R.
The impacts of climate toward tourism sector affect the change in the pattern of tourists' visitation, not only in the scheduling of the time of visit but also in selecting the destination. One of the manifestations of utilizing climate information in the tourism sector is by using the Tourism Climate Index (TCI). The aims of this research are to apply the TCI equation, originally formulated by Mieczkowski in 1985, and to study the appropriateness of this equation to be used in Java and Bali with the current climate settings. By working on observational climate data from a 30-year period, taken from 21 BMKG stations in Java and Bali, it is found that the calculated TCI values are different from what Mieczkowski had produced in 1985, from “Acceptable” category to “Acceptable” and “Unfavourable” category for most of the study areas. Statistically, there was correlation between climate and tourism, that shown by significant value for some sub-index of TCI to visitation. Rainfall is a climate factor that most influnce to visitation pattern in Jawa and Bali.